Exploring the Holistic Benefits of Yoga: A Multi-Method Study - Khatri, Kendra Prakash (Creative Vision: Multidisciplinary Journal of PMC, 2025)
This study investigates the myriad benefits of yoga, examining its long history, profound philosophical basis, and impact on body and mind. Using a mixed-methods approach, such as systematic review of existing published literature, questionnaires, interviews and case studies, it explores how regular practice of yoga helps to increase flexibility, strength, and wellbeing and examines how it helps to reduce stress. Yoga is not merely a form of physical exercise; it provides a holistic way toward a healthy and balanced healthy life. The research crystallizes the scientific wisdom, buttressed by personal experience that yoga provides in terms of mental sharpness, emotional resilience, and improvement in the synergetic functioning of the body with the mind. By synthesizing ancient knowledge and contemporary evidence, the research reveals how yoga can cultivate greater proactivity in living, while serving as an accessible entry-point for individuals of any age, social, or cultural background. The conclusion shows that at the point when yoga is coordinated with life, one's well-being is pushed to the following level and for a lifetime and results in a more astute, supplicating, and secretive way of life.